Valdosta High School Scrapbook 1, September 1960 - January 1961 - Lowndes County Highschool (My University, 1960)
This item contains newspaper clippings of the 1960 football season for Valdosta High School. This season saw the first Triple A state title for Valdosta High School. Basketball is mentioned briefly but is not the focus of this item.
This item contains an 83 page PDF with a title page
Keywords: Newspapers; American Football; Scrapbooks; Photographs